Sosialisasi Pemanfaatan Jus Mentimun dalam Menurunkan Tekanan Darah Pada Penderita Hipertensi - Dian Nurmawati; Siswidiasari, Arifani; Tri Doso Sapto Agus Priyono (LPPM UNINUS, 2025)
Hypertension or high blood pressure, when the results of systolic blood pressure (SBP) measurements are ≥140 mmHg and/or diastolic blood pressure (DBP) are ≥90 mmHg after repeated blood pressure checks. The purpose of this community service activity is to increase insight and knowledge about the use of cucumber juice in lowering blood pressure in hypertension. Cucumber juice is known to be beneficial for lowering blood pressure. Community service activities were carried out in Mojoroto Village RT. 23, RW 4, Kediri City with a total of 30 participants. The method used was Health socialization which was carried out on Saturday, February 22, 2025 in Mojoroto Village. The media used were LCD, projector, and powerpoint. The results of the community service obtained before (pretest), obtained percentage results with a less than 43.33% category, sufficient 33.34% and good 23.33%. After the socialization, the percentage results were categorized as sufficient at 46.6%, good at 40%, and lacking at 13.33%. Conclusion: There was an increase in knowledge before (pretest) and after (posttest) the socialization was given about the use of cucumber juice to lower blood pressure in hypertension sufferers. Keywords: Hypertension, cucumber, blood pressure